THE USE OF SHORT STORY TO INCREASE STUDENTS’ VOCABULARY - Intan Korompot; Paula Hampp; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2022)
A short story is a story that is written shorter than a novel and longer than a fable. Short stories focus on larger or smaller issues and focus on building strong feelings from the readers. A short story tells about one aspect of a character's life. This aspect of life can be an event, a picture of a feeling, or a simple action in the life of a character. Short stories can also influence or even inspire readers. Because it is no longer a taboo if short stories are widely used in the English learning process. One of the important aspects in learning English is Vocabulary. Teaching this aspect is neither easy nor difficult. There are many things that teachers can use to improve vocabulary, because vocabulary in the learning process needs to use appropriate techniques/methods, one of which can use short stories. Therefore, this study wanted to find out how the effect of short stories on increasing students' vocabulary. In the process, this research uses a quantitative approach with a pre-experimental design. In this design, the model is one group pre-test and post-test. 20 students of class VIII A were taken as samples in this study, to calculate the results of the student test, the researcher used the mean score formula to analyze the data. As the results, the short story in the form of a storyline has a lot of vocabulary, so that the students' vocabulary is increasing, this is proven by the significant difference between the students' pre-test and post-test.A short story is a story that is written shorter than a novel and longer than a fable. Short stories focus on larger or smaller issues and focus on building strong feelings from the readers. A short story tells about one aspect of a character's life. This aspect of life can be an event, a picture of a feeling, or a simple action in the life of a character. Short stories can also influence or even inspire readers. Because it is no longer a taboo if short stories are widely used in the English learning process. One of the important aspects in learning English is Vocabulary. Teaching this aspect is neither easy nor difficult. There are many things that teachers can use to improve vocabulary, because vocabulary in the learning process needs to use appropriate techniques/methods, one of which can use short stories. Therefore, this study wanted to find out how the effect of short stories on increasing students' vocabulary. In the process, this research uses a quantitative approach with a pre-experimental design. In this design, the model is one group pre-test and post-test. 20 students of class VIII A were taken as samples in this study, to calculate the results of the student test, the researcher used the mean score formula to analyze the data. As the results, the short story in the form of a storyline has a lot of vocabulary, so that the students' vocabulary is increasing, this is proven by the significant difference between the students' pre-test and post-test.